The quality of corporate governance in South Africa: Comparing the parastatal and listed industrial sectors - Mike F. Van Wyk (South African Journal of Business Management, 1999)
The quality of corporate governance service in the parastatal (also called public entity) and listed industrial company sectors of the South African economy was assessed. The assessment was done using newly developed service quality assessment instruments. The reliability of the findings on the quality of corporate governance service implied a 99.5% probability that the sample mean did not differ from the population mean by more than 0.2 on a seven-point scale. In both sectors the actual corporate governance service was assessed against two levels of expectation, namely the desired service level and the lowest acceptable service level. The instruments were the same except for a few adaptations to cater for the less stringently legislated listed company sector and to provide for insights gained from the first assessment. Both assessments resulted in the same four dimensions, namely 'directing and monitoring', 'board capacity', 'assurance' and 'responsiveness and reliability'. One fundamental difference was reported, namely that the listed company directors' corporate governance was in total, in all four dimensions and on all criteria assessed as between the lowest acceptable and the desired service levels. The public entity directors' corporate governance service was in total, in all four dimensions and on all criteria assessed as below the desired as well as the lowest acceptable service levels. The standard deviations as reported were such that it has to be concluded that acceptable and unacceptable corporate governance service levels are found in public entities as well as in listed companies. The assessment results are reported below graphically. Three criteria appeared on both assessments' lists often worst-assessed criteria. They were directors 'being always properly prepared for meetings', 'doing their homework thoroughly' and 'displaying impeccable integrity and honesty, for example with their own claims'.
Keywords: 650